Governo compartilhado? O papel da presidência na formaç\~ao e coordenaç\~ao da agenda de políticas do executivo federal (2003-2014) - Felix Lopez; Noelle Silva; Jaqueline Borges (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– How the Executive builds its own legislative agenda and which role does the Presidency play? This article partially answers the two questions and specifies how the formulation and the division of labor among its members - parties, bureaucracies, the Presidency and the President - are structured. Even when the President is strong, a coalition government needs to consider other partner's policy and office demands. We identify and translate how and when this process occurs. We collected data from detailed interviews with those who held key positions inside the Presidency or ministries and made documental analyses. The Executive has a dual agenda. The Presidency proposes and conducts a relevant and clearly identifiable part of the policies formulated in the government and, in any case, it is a mediator of the dialogue among cabinet members, before giving the approval for sending the bills to the Congress. The presidential legislative agenda is continuously monitored by Casa Civil while inside the Executive, and has its own timing - faster - and protocols; the "ministerial" agenda follows another one. In both agendas the Presidency gives the last word, building or imposing consensus.
Keywords: Z19; 330; Executive Branch; Presidency of the Republic; Casa Civil; government coordination; coalition presidentialism